Evaluasi Sistem Informasi Akuntansi pada Siklus Pendapatan dan Penerimaan Kas Untuk Mengatasi Kecurangan - Endang Vristia Wati; Linda Lores Purba; Halomoan Situmorang (Economics, Business and Management Science Journal, 2022)
This research was conducted by the author to find out how to evaluate the accounting information system on the cycle of income and cash receipts to overcome fraud at PT. Daehsan Indonesia Medan Branch. This research was conducted to find out about the role of accounting information systems in the cycle of income and cash receipts to overcome fraud at PT. Daehsan Indonesia Medan Branch. The existing accounting information system at PT. Daehsan Indonesia has a very positive effect on supporting the effectiveness of revenue and cash receipts. The author uses a descriptive type of research. The types and sources of data used are primary data, namely data obtained directly from PT. Daehsan Indonesia Medan Branch with interview techniques with the accounting department, documentation techniques to obtain the data needed in writing the thesis and obtain it from the library (library). Based on the results of the Evaluation of Accounting Information Systems on the Cycle of Revenue and Cash Receipts to Overcome Fraud at PT. Daehsan Indonesia Medan Branch, namely the management carried out monitoring and inspection suddenly. So that fraudulent income and cash receipts can be overcome.